Kinetic Analysis of Melon Seed Husk Using Non-Isothermal Thermogravimetric Analysis - Dr. Dodo Yakubu Aminu (Elsevier, 2024)
Materials Today: Proceedings Volume 5, Issue 11, Part 2, 2018, Pages 23249-23257